G242 An exploration of parents' views on shared care in paediatric oncology. (7th April 2014) - Moore, A; Mackinnon, H; Sen, G; King, W
Abstract : Background: The 2005 NICE guidance, 'Improving Outcomes for Children & Young People with Cancer', focused on shared care. The aim is 'safe and effective services as locally as possible, not local services as safely as possible'. Treatment is shared between a specialist principle treatment centre (PTC), a paediatric oncology shared care unit (POSCU) and a community nursing team. Families' views have not been investigated since the 2005 guidance. Aim: To explore parents' views and experiences of care shared between their POSCU, PTC and community nurses. Objectives: To investigate parents' initial experiences, the role of the keyworker, communication issues between teams, and the value of the family held record. Methods: A questionnaire was sent to all parents at one London POSCU whose children had received shared care between 2009 and 2012 and survived treatment. The questionnaire was also available online. 17/39 (44%) parents responded. Results: Parents experienced an initial anxiety and received an explanation of shared care which was too early and inadequate. However due to good relationships with their healthcare teams and key-worker, parents were generally positive. This was maintained by staff members' caring nature and level of knowledge. Parents were dissatisfied when they felt non POSCU/PTC staff did not have adequate specialist knowledge, leading to mistakes. See Image 1 . 47% of respondents were unaware/unsure of who their key-worker was, but identified primary contacts and sources of support. See Image 2 . Parents found the family held record helpful as an organisational tool, but felt its use limited as it was not updated by staff. Communication between healthcare teams was perceived well overall, but where problems occurred this impacted on patient care and parent satisfaction. See Image 3 . Conclusion: Parents' overall had positive perceptions of care shared between three different teams. Recommendations: Parents should be given a clear explanation of how shared care operates and be made aware of the role of their keyworker. Communication of blood results must be maintained and if parents wish to use the family held record, staff should update it regularly. All staff caring for children with cancer should have regular, standardised training to ensure good standards of care throughout the shared care system.